Interpretativne sheme upravljanja s človeškimi viri med gospodarsko krizo - Arzenšek, Ana (Psihološka obzorja (Ljubljana), 2010)
This qualitative research investigates interpretive schemata by producers for automotive industry during the economic crisis in Slovenia. Specifically, the interest was in their Human resource management (HRM) schemata in current crisis. We explained the dynamics of schema change on the basis of Piaget's theory of adaptation. In-depth interviews with CEOs, directors of HRM and leaders of trade unions served as a primary data source. In addition, comparative analysis of social responsibility as reported in companies' annual reports in 2007 and 2008 was made. Firstly, results demonstrate strategic role of HRM in chosen companies. Secondly, present economic crisis does not serve as a factor of schema change. In conclusion, participants mostly assimilate new information from environment to fit their HRM schemata. Results show the major factor for both assimilation and lack of schema change is occurrence of crisis in Slovenian companies that produce for automotive industry in the nineties.
Keywords: človeški viri; management; upravljanje; gospodarska kriza; automotive industry; avtomobilska industrija; sheme; akomodacija; asimilacija; assimilation